Regionalizmy poznańskie w Wielkim słowniku języka polskiego PAN pod redakcją Piotra Żmigrodzkiego (na tle praktyki rejestrowania wielkopolanizmów w słownikach ogólnych języka polskiego) - Piotrowska-Wojaczyk, Agnieszka (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2025)
The aim of the presented text is to show the functioning of the Poznań regionalisms in Wielki Słownik Języka Polskiego PAN (Polish Academy of Sciences’s Great Polish Dictionary) edited by Piotr Żmigrodzki against the background of the practice of registering the regionalisms of Greater Poland in general Polish language dictionaries, from the dictionaries of the New Poland to the dictionaries from the beginning of the 21st century. The comparison of 20 Poznań regionalisms listed in WSJP PAN with their attestations in earlier works proves conclusively that regional Polish is still a living variety of the language. The dictionary edited by Żmigrodzki qualifies in this way, to a large extent, the new units, not included at all in the earlier works or noted in them without any information on their geographical character. This practice applies to 14 entries, i.e. 70% of the selected Greater Poland regionalisms. On the other hand, only 6 words continue their regional characterisation from earlier works, although they were noticed in them very inconsistently. Moreover, an analysis of the lexicographic metrics of the Greater Poland regionalisms proves the changes in their meanings – the disappearance of old meanings, now often obsolete, and the appearance of new ones.